2017
DOI: 10.1177/0193945917697664
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obesity Among Youth With Intellectual and Developmental Disabilities: An Emerging Role for Telenursing

Abstract: Childhood obesity is a serious health issue, associated with medical comorbidity and psychosocial impairment that can persist into adulthood. In the United States, youth with intellectual and developmental disabilities are more likely to be obese than youth without disabilities. A large body of evidence supports the efficacy of family-based treatment of childhood obesity, including diet, physical activity, and behavior modification, but few interventions have been developed and evaluated specifically for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 97 publications
0
16
0
5
Order By: Relevance
“…A study in the UK also reported that the prevalence rates of obesity and overweight were 20.7% and 28.0%, respectively, whereas subjects that fell in the normal range of weight accounted for 32.7% [ 11 ]; a study by Hsieh et al [ 36 ] on people with intellectual disabilities in the United States reported prevalence rates of 28.9% for overweight and 38.3% for obesity. The prevalence of overweight and obesity is higher among people with intellectual disabilities than in the general population [ 12 , 13 , 37 , 38 ]. This may be because people with intellectual disabilities have decreased income levels in an environment where they have difficulty engaging in economic activities, which leads to a lack of opportunities to participate in physical activities and exercise programs [ 20 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in the UK also reported that the prevalence rates of obesity and overweight were 20.7% and 28.0%, respectively, whereas subjects that fell in the normal range of weight accounted for 32.7% [ 11 ]; a study by Hsieh et al [ 36 ] on people with intellectual disabilities in the United States reported prevalence rates of 28.9% for overweight and 38.3% for obesity. The prevalence of overweight and obesity is higher among people with intellectual disabilities than in the general population [ 12 , 13 , 37 , 38 ]. This may be because people with intellectual disabilities have decreased income levels in an environment where they have difficulty engaging in economic activities, which leads to a lack of opportunities to participate in physical activities and exercise programs [ 20 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these may be problematic for children with ASD, who struggle with social and behavioral communication, changes in routine, and sensory processing difficulties [24,68]. Furthermore, challenges with self-management and, in many cases, impairments in decision-making skills play an important role in the challenges associated with this first line of treatment in children with ASD [219]. The second line of intervention is through common pharmacological treatments for childhood obesity, such as orlistat, sibutramine, and metformin.…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%
“…Furthermore, adolescents are more likely to have remission of type 2 diabetes and hypertension after bariatric surgery, when compared to adults [227], emphasizing that optimal timing for surgery in order to reverse metabolic complications of obesity is still unclear. Furthermore, little research has been done in this area to address treatment needs that may be specific to this population [219]. A systematic review looking more broadly at children with intellectual disabilities suggested the need for further research into how obesity treatment can be more specifically tailored for children with intellectual disabilities [219].…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles focus on children with special needs, an often overlooked group at increased risk for this chronic disease. Bennett, Kolko, Chia, Elliott, and Kalarchian (2017) review studies that evaulated treatment strategies for youth with intellectual and developmental disabilities. The second study (Polfuss, Simpson, Greenley, Zhang, & Sawin, 2017) focuses on parents of children who were diagnosed with autism, spina befida, or Down's Syndrome.…”
mentioning
confidence: 99%